2021
DOI: 10.3389/fonc.2021.642919
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal Invasion, but Not Incomplete Excision, Has Negative Impact on Long-Term Survival in Patients With Extramammary Paget’s Disease

Abstract: BackgroundExtramammary Paget’s disease (EMPD) sometimes spreads from the skin to mucosal areas, and curative surgical excision of these areas is challenging. The aim of this study is to analyze the impact of mucosal involvement and surgical treatment on the survival of patients with EMPD.MethodsWe conducted a retrospective review of 217 patients with EMPD. We also assessed the associations between tumor involvement in boundary areas (anal canal, external urethral meatus, vaginal introitus), prognostic factors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 41 publications
0
12
1
Order By: Relevance
“…The prognosis of EMPD is relatively good, 6 and it has been reported that incomplete excision of primary tumors does not statistically correlate with worse disease-specific survival nor is such excision a poor prognostic factor, compared with complete removal. 12 In this study, there were no significant differences in OS or MFS between the conservative excision group and the wide excision group, which suggests that local management of the primary tumor is not directly related to EMPD metastasis and prognosis. In addition, the subgroup analysis of the cases with a follow-up period of at least 24 months revealed that there were no significant differences in OS between the 2 groups, although MFS was shorter for the conservative excision group.…”
Section: Discussionmentioning
confidence: 47%
“…The prognosis of EMPD is relatively good, 6 and it has been reported that incomplete excision of primary tumors does not statistically correlate with worse disease-specific survival nor is such excision a poor prognostic factor, compared with complete removal. 12 In this study, there were no significant differences in OS or MFS between the conservative excision group and the wide excision group, which suggests that local management of the primary tumor is not directly related to EMPD metastasis and prognosis. In addition, the subgroup analysis of the cases with a follow-up period of at least 24 months revealed that there were no significant differences in OS between the 2 groups, although MFS was shorter for the conservative excision group.…”
Section: Discussionmentioning
confidence: 47%
“…There are few reports on surgical margins and survivalof EMPD. Some studies reported no association between surgical margins and survival in patients with vulvar EMPD 14,15 …”
Section: Discussionmentioning
confidence: 99%
“…In clinical settings, EMPD is curable when surgically eradicated in the early stage because the tumors generally exhibit slow growth and a long dormant phase [ 4 , 44 ]. However, complete surgical removal is sometimes difficult because of diagnostic delays or anatomical constraints, leading to an increased risk of metastasis [ 4 , 10 ]. Conventional chemotherapy with taxanes, platinum-containing drugs, 5-fluorouracil, epirubicin, vincristine, and mitomycin C has been to treat metastatic EMPD, but the efficacy is unsatisfactory [ 4 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 15–40% of EMPD lesions exhibit dermal invasion in their clinical course, increasing the risk of lymph node and distant metastasis [ 2 , 4 ]. Although complete surgical removal is the treatment of choice for resectable EMPD, this is sometimes difficult to achieve because of the inconspicuous tumor border and anatomical constraints [ 9 , 10 ]. The prognosis of unresectable EMPD is poor once the tumor metastasizes because of the lack of effective systemic therapies [ 4 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%